Atlas of tropical medicine and parasitology - Peters, Wallace; Pasvol, Geoffrey (Elsevier/Mosby, 2007)
This book is a visual treat. This is a well-constructed book where the authors have decided to structure the information on the mechanism of transmission of the disease. This allows for a sensible consistency in presentation which may not please those who like a breakdown of disease on the basis of the type of organism or organ affected.